Lex Sportiva and Lex Ludica: The Existence and Reconstruction of Sports Law Principles in the Postmodern Era - Dicky Eko Prasetio; Muhammad Akmal Habib (Universitas Negeri Surabaya, 2025)
Sports law is a relatively new field that examines the legal aspects of sports, which is experiencing increasingly rapid development, particularly in the postmodern era. The principles of lex sportiva and lex ludica are fundamental in the field of sports law, but in practice, they often clash. This research aims to analyze and reflect on these principles as important foundations in Indonesian sports law in the postmodern era, viewed from the perspective of legal philosophy. This research is normative legal research that examines aspects of legal philosophy, so its orientation is not merely normative-doctrinal, but also reflective. The research findings confirm that the development of sports law in the postmodern era shows a significant increase, characterized by the emergence of the idea of legal pluralism, where non-state law plays an important role as a complement and counterbalance to state law. The fundamental essence of these principles reflects the plural and complex dynamics of law, where both principles possess their own autonomy and independence, complementing each other within the sports legal system. This research recommends strengthening the understanding of legal pluralism and clarifying the lex sportiva, which is related to its general characteristics, while the lex ludica emphasizes the independence and autonomy of game law in each sport.